THE POWER OF FOOD: SHAPING IDEOLOGIES, CULTURE AND WAYS OF LIFE. (International Journal of Food and Nutritional Sciences, 2022)
Food is an integral part of our daily lives, but it is not just a source of sustenance. It is also a cultural artefact, a symbol of identity, and a means of communication. The philosophy of food is a relatively new field of study that explores the complex relationships between food, culture, and society. It seeks to understand food's ethical, social, and cultural dimensions and examine how food shapes our lives and world. The philosophy of food is an interdisciplinary field that draws on insights from philosophy, anthropology, sociology, history, and other disciplines. It asks fundamental questions about the nature of food, such as what makes food good or bad, the relationship between food and health, and the role of food in human flourishing. It also explores cultural and social dimensions, such as how food expresses identity, shapes social relationships, and reflects broader cultural values and beliefs. In this article, we will explore food philosophy in more detail, examining the key questions and debates in the field. We will look at the ethical dimensions of food, including issues such as food justice, animal welfare, and environmental sustainability. We will also examine food's cultural and social dimensions, exploring how food expresses identity, shapes social relationships, and reflects broader cultural values and beliefs. Finally, we will consider the role of food in the human way of life, examining the relationship between food and health and how food can contribute to a good life. The philosophy of food explores the ethical, cultural, and social implications of food and eating, and it seeks to understand the role of food in shaping our lives and our society.